A Virtual Representation of the Egyptian Cultural Heritage - Fathi Saleh (Virtual Archaeology Review)
In Egypt, the Center for Documentation of Cultural and Natural Heritage (CULTNAT) is treating cultural heritage in a holistic approach whether regarding the diversity of themes of cultural heritage or in the case of museums, the presence of objects in the different museums both within the country or abroad (a sort of global virtual museum). The establishment of CULTNAT marks a unique experience in the application of the latest innovations in the world of telecommunications and information technology towards heritage issues. CULTNAT’s main mandate is to document the various aspects of Egypt's tangible and intangible cultural heritage as well as its natural heritage.